Plasma Cell Mucositis of Oro- and Hypopharynx: A Case Report. (17th June 2012) - Puvanendran, Mark; Lieder, Anja; Issing, Wolfgang
Abstract : Objective . To raise awareness of plasma cell mucositis as a rare differential diagnosis for oral mucosal ulceration and its macroscopic similarity to malignancy. Method . We report a patient who presented with oral features suggestive of malignancy. A biopsy revealed plasma cell mucositis. Results . The patient successfully had a full excision of one lesion and a spontaneous resolution of the other. Conclusion . With the increasing incidence of oral mucosal pathology, physicians should be aware of this differential diagnosis.